THE ROLE OF THE LAOS NATIONAL DISASTER MANAGEMENT COMMITTEE (NDMC) IN DISASTER MANAGEMENT IN LAOS IN 2018 TO SUPPORT NATIONAL SECURITY - Ketsana Sengdara; Achmed Sukendro Achmed Sukendro; Heridadi Heridadi; Wilopo Wilopo, S.E., MM., M.Han. (Republic of Indonesia Defense University, 2023)
Laos is a landlocked country that has no maritime boundaries with other countries. Although Laos is a country that rarely experiences disasters, in 2018 there was a flash flood that hit the province of Attapeu. The flash flood resulted in 49 deaths and 22 missing people and resulted in various losses suffered. The Lao National Disaster Management Committee has a great responsibility to carry out disaster management in Laos so that disaster risks can be minimized. The purpose of this study was to determine the role of the Lao National Disaster Management Committee in the disasters that occurred in 2018. The methodology used in this study used a descriptive qualitative research methodology based on a literature review. The results of this study reveal the various efforts made by the Lao National Disaster Management Committee at each stage of disaster management. In the Surveillance, Monitoring and Alert stage, the focus is on monitoring, monitoring and early warning of disasters that may occur naturally. Then at the stage of The Control and Provision of Emergency Aid During the Disaster Incidents, what is done is the control and provision of emergency assistance during disaster incidents. In the Disaster Recovery stage, repair, build and restore infrastructure affected and or damaged by the disaster back to a normal or even better situation.